Analisis Dan Perancangan Sistem Informasi Kepegawaian Berbasis Web Pada Kantor Komisi Pemilihan Umum Kota Jambi - Sufadmi, Hery; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2020)
Office of Komisi Pemilihan Umum Kota Jambi has problems relating to staffing, which led to employee difficulties to find information and access to information related to staffing, as well as the operators often lost files relating employment due to frequent data redundancy, the data are inconsistent (inconsistent data), data stored irregularly , the data is less secure, because data is only stored on one computer only (standalone). The objectives to be achieved in this research are to analyze the system requirements and design a Web-Based Personnel Information System to produce prototype documentation of the Personnel Information System. The process of the analysis and design of systems using modeling system based on the Unified Modeling Language (UML), while designing the prototype using tools balsamiq mockups. The expected outcome of this research is to become a reference for solving problems related to staffing at the Komisi Pemilihan Umum Kota Jambi.